Novel lineages of bacteria with reduced genomes from the gut of farm animals - Shahjahon Begmatov; Alexey V. Beletsky; Andrey V. Mardanov; Anastasia P. Lukina; Liubov B. Glukhova; Olga V. Karnachuk; Nikolai V. Ravin (mSphere)
ABSTRACT Genome reduction and associated metabolic deficiencies have been described in various lineages of parasitic and symbiotic microorganisms that obtain essential nutrients from their partners, and in some free-living microorganisms that inhabit stable environments. The animal gut is a relatively stable ecosystem, characterized by an abundance of organic substances and a high concentration of microorganisms, which provides favorable conditions for the survival of microorganisms with reduced genomes. Metagenomic analysis of 49 samples of feces of farm animals (cows, sheep, yaks, and horses) revealed uncultured lineages of bacteria with reduced genomes (<1 Mbp): family UBA1242 (Christensenellales, Firmicutes), order Rs-D84 (Alphaproteobacteria), and family UBA9783 (Opitutales, Verrucomicrobiota), defined in genome-taxonomy database. Analysis of the genomes showed that these bacteria lacked pathways for the biosynthesis of amino acids, nucleotides, lipids, and many other essential metabolites. The UBA9783 genomes encoded a near-complete Embden-Meyerhof glycolytic pathway and the non-oxidative phase of the pentose phosphate pathway, while in UBA1242 and Rs-D84, these pathways are incomplete. All bacteria are limited to fermentative metabolism and lack aerobic and anaerobic respiratory pathways. All UBA9783 and some Rs-D84 genomes encoded F0F1-type ATP synthase and pyrophosphate-energized proton pump; they also can import and utilize peptides and some amino acids. While UBA9783 bacteria could thrive as specialized free-living organisms in the organic-rich gut environment, the UBA1242 and Rs-D84 lineages appear to have adopted the lifestyle of an obligate symbiont/parasite, obtaining metabolites from other cells.IMPORTANCEThe microbiota of the animal gastrointestinal tracts is a complex community of microorganisms which interact in a synergistic or antagonistic relationship and play key nutritional and metabolic roles. However, despite its importance, the gut microbiota of farm animals, especially its uncultured majority, remains largely unexplored. We performed a metagenomic analysis of the gut microbiome of farm animals and characterized three uncultured lineages of bacteria with reduced genomes (<1 Mbp) from the phyla Firmicutes, Proteobacteria, and Verrucomicrobiota. These bacteria were predicted to possess key metabolic deficiencies such as the inability to synthesize essential cell metabolites, suggesting their adaptation to the lifestyle of a symbiont/parasite, or a scavenger obtaining nutrients from the organic-rich gut environment. This study shows that genome reduction with metabolic specialization and adaptation to a partner-dependent lifestyle occurred through convergent evolution in several phylogenetically distant lineages of gut microbiota.